Unveiling the Black Box: How Employer Branding Drives Employee Engagement - Evidence from PT Gardamas Surya Lestari, Indonesia - Ramadhan, Sarah; Sinaga, Vera Juliana; Dwianto, Agung Surya (Program Studi Manajemen, Fakultas Ekonomi, IBI-K57, 2024)
The global competition for top talent is intensifying. Employer branding, as a strategy to build a company's image as an attractive place to work, is becoming increasingly important in attracting and retaining quality employees. However, there are still few studies that examine how employer branding specifically drives employee engagement in Indonesia. This research aims to understand how employer branding drives employee engagement at PT Gardamas Surya Lestari, Indonesia. This research uses a qualitative method with a single case study. Data was collected through in-depth interviews with the Company Leader, HRD Manager and Employees of PT Gardamas Surya Lestari. The results showed that employer branding of PT Gardamas Surya Lestari has a positive influence on employee engagement. This is achieved through three main mechanisms: First, building a strong corporate identity and values: PT Gardamas Surya Lestari has built a strong corporate identity and values, which are consistently communicated to employees through various channels. Second, creating a positive work culture: The work culture at PT Gardamas Surya Lestari supports employee engagement by providing employees with opportunities to learn and develop, and feel valued and respected. The third research result is by offering attractive programmes and benefits: PT Gardamas Surya Lestari offers attractive programmes and benefits for employees, including competitive salaries and benefits, career development opportunities, and a conducive work environment.